2019
DOI: 10.1111/jfpe.13020
|View full text |Cite
|
Sign up to set email alerts
|

Thin layer drying kinetics of Banana var. Monthan (ABB): Influence of convective drying on nutritional quality, microstructure, thermal properties, color, and sensory characteristics

Abstract: Banana with good amount of resistant starch (RS) offers greater benefit to human health. Studying the dehydration mechanism of the raw banana slice is very important for subsequent processes and quality of the product. Thus the study was aimed to investigate the influence of varying temperatures viz., 45, 55, and 65°C in a convective dryer on thin layer drying kinetics and to infer their influence on the rheological properties coupled thermal and sensory quality. Time for reducing the moisture content from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
31
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 37 publications
7
31
0
2
Order By: Relevance
“…Furthermore, it was observed that higher temperatures resulted in higher DR. The same fact was observed by Kumar et al (2019), on drying bananas.…”
Section: Resultssupporting
confidence: 86%
See 4 more Smart Citations
“…Furthermore, it was observed that higher temperatures resulted in higher DR. The same fact was observed by Kumar et al (2019), on drying bananas.…”
Section: Resultssupporting
confidence: 86%
“…The shortest drying time was obtained using the highest temperature. The same was observed by Thuwapanichayanan, Prachayawarakorn, Kunwisawa, and Soponronnarit (2011), Song et al (2019) and Kumar et al (2019).…”
Section: Resultssupporting
confidence: 81%
See 3 more Smart Citations